(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
"The Godfather," a seminal work in literature, transcends its portrayal of organized crime to emerge as a profound political narrative. This novel delves into the intricate dynamics of power, loyalty, and influence, offering a compelling commentary on the nature of governance and authority. Through the lens of the Corleone family, the story reveals the parallels between the Mafia’s internal operations and broader political structures, illustrating how power is consolidated, challenged, and maintained. The Godfather serves as a microcosm of political machinations, exploring themes such as the corruption of power, the moral ambiguities in leadership, and the role of familial loyalty in political strategy. This analysis highlights how "The Godfather" functions not only as a crime novel but also as a significant political allegory that resonates with real-world governance.